EXARC at the Times and Epochs Festival, Kolomenskoye Park, Moscow - Bill Schindler (EXARC Journal)
As an EXARC Board member, I attended the Times and Epochs Festival in Moscow from June 21-23, 2013 in the open-air museum Kolomenskoye Park. This year, an estimated 200,000 people attended the medieval themed festival where they were able to witness and interact with 2,000 re-enactors from 40 different countries demonstrating period and place correct blacksmithing, pottery, wood-carving, felting, jewelry making, boat building, and a variety of other skills. There were also jousting tournaments, and full combat demonstrations in the arena. Many of these re-enactors were highly skilled and the manner in which they interacted with the public, especially children, was truly impressive. In addition to watching artisans demonstrating their crafts, stations were set up for kids to try their own hand as felting, blacksmithing, pottery, wood-carving and archery.